Picnic at Hanging Rock - Lindsay, Joan 1896-1984 (Penguin Random House, 2013)
If her terrified cries had been heard by anyone but a wallaby squatting in a clump of bracken a few feet away, the picnic at Hanging Rock might yet have been just another picnic on a summer's day. On a cloudless summer day in 1900, a group from Appleyard College for Young Ladies goes for a picnic. In the heat of the afternoon sun, three girls climb through the scrub-and disappear. Ethereal and enigmatic, Picnic at Hanging Rock has been haunting the Australian imagination for half a century
Keywords: Young women / Australia / Victoria / Fiction; Schoolgirls / Australia / Victoria / Fiction; Missing persons / Fiction; Australian fiction; Hanging Rock (Vic.) / Fiction; Jeunes femmes / Australie / Victoria / Romans, nouvelles, etc; Écolières / Australie / Victoria / Romans, nouvelles, etc; Personnes disparues / Romans, nouvelles, etc; Roman australien; Missing persons; Schoolgirls; Young women; Victoria / https://id.oclc.org/worldcat/entity/E39QbtfRDdrtgyXybc3cCkCJ9c; Fiction